Intracerebral gene therapy in children with mucopolysaccharidosis type IIIB syndrome: an uncontrolled phase 1/2 clinical trial. Issue 9 (September 2017) - Tardieu, Marc; Zérah, Michel; Gougeon, Marie-Lise; Ausseil, Jérome; de Bournonville, Stéphanie; Husson, Béatrice; Zafeiriou, Dimitrios; Parenti, Giancarlo; Bourget, Philippe; Poirier, Béatrice; Furlan, Valérie; Artaud, Cécile; et al.
Summary: Background: Mucopolysaccharidosis type IIIB syndrome (also known as Sanfilippo type B syndrome) is a lysosomal storage disease resulting in progressive deterioration of cognitive acquisition after age 2–4 years. No treatment is available for the neurological manifestations of the disease. We sought to assess the safety and efficacy of a novel intracerebral gene therapy. Methods: Local regulatory authorities in France allowed inclusion of up to four children in this phase 1/2 study. Treatment was 16 intraparenchymal deposits (four in the cerebellum) of a recombinant adenoassociated viral vector serotype 2/5 (rAAV2/5) encoding human α-N-acetylglucosaminidase (NAGLU) plus immunosuppressive therapy. We assessed tolerance, neurocognitive progression, brain growth, NAGLU enzymatic activity in CSF, and specific anti-NAGLU immune response for 30 months after surgery. This trial is registered with EudraCT, number 2012-000856-33, and the International Standard Clinical Trial Registry, number ISRCTN19853672. Findings: Of seven eligible children, the four youngest, from France (n=2), Italy (n=1), and Greece (n=1), aged 20, 26, 30, and 53 months, were included between February, 2012, and February, 2014. 125 adverse events were recorded, of which 117 were treatment emergent and included six classified as severe, but no suspected unexpected serious adverse drug reactions were seen. Vector genomes were detected in blood for 2 days after surgery. Compared with the natural history of mucopolysaccharidosis type III syndromes, neurocognitive progression was improved in all patients, with the youngest patient having function close to that in healthy children. Decrease in developmental quotient was −11·0 points in patient one, −23·0 in patient two, −29·0 in patient three, and −17·0 in patient four, compared with −37·7 in the natural history of the disease. NAGLU activity was detected in lumbar CSF and was 15–20% of that in unaffected children. Circulating T lymphocytes that proliferated and produced tumour necrosis factor α upon ex-vivo exposure to NAGLU antigens were detectable at 1–12 months and 3–12 months, respectively, but not at 30 months in three of four patients. Interpretation: Intracerebral rAVV2/5 was well tolerated and induced sustained enzyme production in the brain. The initial specific anti-NAGLU immune response that later subsided suggested acquired immunological tolerance. The best results being obtained in the youngest patient implies a potential window of opportunity. Longer follow-up is needed to further assess safety outcomes and persistence of improved cognitive development. Funding: Association Française Contre les Myopathies, Vaincre les Maladies Lysosomales, Institut Pasteur, and UniQure.